Glucocorticoid Induced Compression Fractures in a Patient with Pemphigus Vulgaris - Sabaz, Emel; Karaca, Günseli; Yıldırım, Arefe; Özgöçmen, Salih (Fırat University, 2007)
Osteoporosis is recognized as primary or secondary related to various factors. Herein we presented a patient who developed osteoporosis and compression fractures related to high dose steroid treatment. Sixty-three years old female patient attended to our outpatient clinic with complaints of back and low back pain, and she had a history of high dose steroids for the treatment of pemphigus vulgaris. She had multiple compression fractures of the thoracic vertebrae. Bone mineral density revealed a T score of -2.3 for lumbar and -1.6 for femoral neck regions. Upon examination compression fractures were considered to be related to high dose glucocorticoid treatment. As a consequence; osteoporosis should not be overlooked in established and high dose corticosteroid treatment particularly in postmenopausal female and patients should be screened for osteoporosis prior to treatment and prophylaxis should be maintained if necessary. ©2007, Fırat University, Medical Faculty

Osteoporoz, primer ve pek çok ikincil sebeplerle oluşan sekonder osteoporoz olarak ayrılabilir. Burada yüksek doz steroid kullanımı sonucu osteoporoz ve kompresyon fraktürleri gelişmiş bir hastayı sunmaktayız. Altmış üç yaşında kadın hasta polikliniğimize sırt ve bel ağrısı şikayeti ile başvurdu. Hastada pemfigus vulgaris nedeniyle yüksek doz steroid kullanma öyküsü mevcuttu. Çekilen grafisinde torakal bölgede multipl kompresyon fraktürleri mevcuttu. Çekilen kemik dansitometrisinde L2-4 vertebra T skoru -2.3, total femur T skoru -1.6 olarak saptandı. Olgu değerlendirildiğinde oluşan osteoporoz ve kompresyon fraktürlerinin kronik yüksek doz steroid kullanımına bağlı olabileceği düşünüldü. Burada uzun dönem steroid kullanması gereken hastalarda sekonder osteoporozun göz ardı edilmemesi gerektiği; özellikle postmenapozal hastalarda tedaviye başlanmadan önce hastanın osteoporoz açısından değerlendirilmesi ve gerektiğinde proflaksi başlanmasının önemi vurgulanmaktadır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Pemfigus Vulgaris Hastasında Glukokortikoid Kullanımına Bağlı Oluşan Kompresyon Fraktürleri